Magnetoresistance oscillations up to 32 K in the organic metal β″-(ET)4(H3O)[Fe(C2O4)3]·C6H4Cl2: Органические проводники - Laukhin, Vladimir N.; Audouard, Alain; Vignolles, David; Canadell, Enric; Prokhorova, Tatyana G.; Yagubskii, Eduard B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Magnetic torque and magnetoresistance of the quasi-two-dimensional charge transfer salt β″-(ET)4(H3O)[Fe(C2O4)3]·C6H4Cl2 have been investigated in pulsed magnetic fields of up to 55 T. At variance with de Haas–van Alphen oscillations, Shubnikov–de Haas oscillations are observed up to temperatures as high as 32 K at ambient pressure despite a significant thermal damping in the low-temperature range. This feature, observed under applied pressure as well, is interpreted on the basis of the coexistence of a closed orbit and a quantum interference path with the same cross section.